INVESTIGATION OF THE EFFECT ON OVERALL HEAT TRANSITION COEFFICIENT AND HEAT LOSS OF WALL APPLİCATİONS WİTH SANDWISH AND AERATED CONCRETE - Aksoy, U. Teoman (Erciyes Üniversitesi, 2008)
This study was investigated overall heat transition coefficient (Uove) and heat lost (Q) of sandwich and gasconcrete walls in the a cold city of Turkey like Elazığ (TS 825-3.Region). In study was compareted the present applications and applications in the regulation. Overall U values and heat lost were calculated with Ts 825 method. In present applications of gasconcrete and sandwich wall, the Uove values are determined as 0.99 and 1.21 W/m2 K, 0.94-1.13 W/m2 K respectively. If wall applications designed according to U value of 0.5 W/m2 K for the 3 region, heat losses would decrease approximately 35-55 %

Bu çalışmada, Türkiye’nin soğuk şehirlerinden biri olan Elazığ’daki (TS 825-3.Bölge) sandviç ve gazbeton duvar uygulamalarının, ortalama ısı geçirgenlik katsayısı (Uort) ve ısı kaybı (Q) araştırılmıştır. Mevcut durum ve yönetmelikteki uygulamaların ortalama U-değerleri ve ısı kaybı hesaplanmış ve karşılaştırılmaları yapılmıştır. Duvar uygulamalarının ortalama U-değerleri ve ısı kaybı TS 825’e göre hesaplanmıştır. Mevcut durum, gazbeton duvar uygulamalarında Uort=0.99 ve 1.21 W/m2 K ve sandviç duvar uygulamalarında ise Uort=0.94-1.13 W/m2 K olarak hesaplanmıştır. 3. bölge için istenen U=0.5 W/m2 K göre detaylandırılan, duvar uygulamalarında ısı kayıplarının yaklaşık % 35-55 azaldığı tespit edilmiştir.
SANDVİÇ VE GAZBETON DUVAR UYGULAMALARININ ORTALAMA ISI GEÇİRGENLİK KATSAYISI VE ISI KAYBI ÜZERİNDEKİ ETKİSİNİN İNCELENMESİ